The development strategies of high speed railway new towns in China: Wuxi East new town - Pan, Qiongyu (2017)
Since the first high speed railway came into operation in 2008, China has stepped into a new era of rapid development based on efficient transport connections and a strong economic engine. Subsequently, an unprecedented urban extension campaign of ‘High Speed Railway New Town’ emerged and has attracted immense attention. Local governments have demonstrated great ambitions on urban development around high speed rail stations and shown huge enthusiasm for its potential. A great many cities with connection to high speed rail have set up grand plan and design for the so called ‘High Speed Rail New Town’. Although authorities tend to put great confidence in HSR construction and station area development, the process is, in fact, by no means easy. It is a rather tortuous and complicated process, full of fierce debate, conflicts of interest and ambiguous impact. The major objective of this thesis is to investigate the current development strategies of high speed railway new towns in China in relation to their node value and place value, with the ultimate intention to provide guidelines for the rational development process for this new type of urban settlement. A specific case, Wuxi East New Town, as the earliest constructed ‘High Speed Railway New Town’ in China with the fastest development speed at present, was selected and critically explored to show the current development picture and evaluate its strength and weakness. Due to the uniqueness and the initial development stage of ‘High Speed Railway New Town’ in China, comprehensive lessons from international experience in new town development and urban development around high speed railway stations were critically studied. Hence, synthesising existing literature and knowledge related to China's HSR New Town and relating this to international experience is an important and original contribution to the research.